Determinants of plant closures in Swedish manufacturing - Fredrik Andersson; Altin Vejsiu (Institute for Labour Market Policy Evaluation (IFAU), 2001)
We study the derminants of plant closures i Swedish manufacturing using linked employer-employee data. From our theoretical framework we derive and empirically test hypothesis regarding the linkages between the probability of plant failure and: 1) industry-specific characteristics of production and product demand; 2) local labor market conditions; and 3) plant-specific sources of heterogeneity, including the importance of insider mechanisms in wage determination, plant specific human capital, selection mechanisms and technology vintage effects. Our results suggest that all these factors matter in ways that by and large conform to the a priori hypotheses.
Keywords: J21; J23; 330; Plant closures; job reallocation; insider wage determination; selection mechanisms; capital vintage effects; linked employer-employee data